Modelling Crack Growth in Additively Manufactured Inconel 718 and Inconel 625 - Rhys Jones; Andrew Ang; Daren Peng; Victor K. Champagne; Alex Michelson; Aaron Birt (Metals, 2023)
This paper first examines crack growth in a range of tests on additively manufactured (AM) and conventionally manufactured Inconel 718. It is shown that whereas when the crack growth rate (da/dN) is plotted as a function of the range of the stress intensity factor (ΔK), the crack growth curves exhibit considerable scatter/variability, when da/dN is expressed in terms of the Schwalbe crack driving force (Δκ), then each of the 33 different curves essentially collapse onto a single curve. This relationship appears to hold over approximately six orders of magnitude in da/dN. The same phenomenon also appears to hold for 20 room temperature tests on both conventionally and additively manufactured Inconel 625. Given that the 53 studies examined in this paper were taken from a wide cross section of research studies it would appear that the variability in the da/dN and ΔK curves can (to a first approximation) be accounted for by allowing for the variability in the fatigue threshold and the cyclic fracture toughness terms in the Schwalbe crack driving force. As such, the materials science community is challenged to address the fundamental science underpinning this observation.